British Association for Irish Studies Executive elections 1992. Guidance on ballot (amended) - British Association for Irish Studies, BAIS (1992)
BAIS (British Association for Irish Studies) executive elections 1992 typescript guidance on ballot. Deadline stated 21 October 1990 (amended by hand). Manuscript note on the bottom from 'Jim' to 'Mary'.